1985
DOI: 10.1083/jcb.101.6.2210
|View full text |Cite
|
Sign up to set email alerts
|

Cell-mediated extracellular acidification and bone resorption: evidence for a low pH in resorbing lacunae and localization of a 100-kD lysosomal membrane protein at the osteoclast ruffled border.

Abstract: The extracellular compartment where bone resorption occurs, between the osteoclast and bone matrix, is shown in this report to be actively acidified. The weak base acridine orange accumulates within this compartment but dissipates after incubation with ammonium chloride. Upon removal of ammonium chloride, the cells are able to rapidly reacidify this compartment. The highly convoluted plasma membrane of the osteoclast facing this acidic compartment (ruffled border) is shown to contain a 100-kD integral membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
338
0
6

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 690 publications
(354 citation statements)
references
References 44 publications
10
338
0
6
Order By: Relevance
“…Generation of a continuous proton gradient across the osteoclastic ruffled border domain is critical to its resorptive function (2,5). Previous studies have shown that various V-ATPase subunits play important roles in osteoclast differentiation and function (9, 24, 39).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generation of a continuous proton gradient across the osteoclastic ruffled border domain is critical to its resorptive function (2,5). Previous studies have shown that various V-ATPase subunits play important roles in osteoclast differentiation and function (9, 24, 39).…”
Section: Discussionmentioning
confidence: 99%
“…The ruffled border is the "resorptive organelle" of the osteoclast and is formed by the polarized targeting and fusion of acidified intracellular vesicles with the plasma membrane (2)(3)(4). These transport vesicles courier acidifying machineries as well as osteolytic enzymes such as, TRACP, cathepsin K, and matrix metalloproteinases (2,(5)(6)(7) to the ruffled border membrane domain where each cargo plays a discrete role in the resorptive function. Vacuolar H ϩ -adenosine triphosphatases (V-ATPases) 5 that line the ruffled border have long been established to play a vital role in the resorptive process.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…V-ATPase has been purified from endomembrane systems including lysosomes, chromaffin granules, endosomes, synaptic vesicles and clathrin-coated vesicles (Mellman et al, 1986;Arai et al, 1987a;Nelson, 1989;Moriyama and Nelson, 1989;Futai, 1990, Arai et al, 1993). In addition, V-ATPase also has been detected in the plasma membrane of a few specalised cell types including osteoclasts (Baron et al, 1985;Akisaka and Gay, 1986;Vaananen et al, 1990), macrophages (Swallow et al, 1990;Bidani and Brown, 1992;Tapper and Sundler, 1992), activated neutrophils (Nanda et al, 1992), renal intercalated cells (Verlander et al, 1991) and some tumour cell lines (Martinez-Zaguilan et al, 1991).…”
mentioning
confidence: 99%
“…44 In addition, while in most cell types expression of lysosomal hydrolases is intralysosomal, in osteoclasts, the lysosomal hydrolases are expressed at the ruffled border. 13,86,105 This results in the unique manifestation of skeletal lesions seen in several lysosomal storage diseases.…”
Section: Morphological Biochemical and Molecular Biology Approachesmentioning
confidence: 99%